Manajemen Evaluasi Pembelajaran dalam Meningkatkan Mutu Lulusan di Lembaga Studi Bahasa Arab Ma'had Al-Birr Makassar - Rabiah Syam; M. Ilham Muchtar; Hasan bin Juhanis (IAIN Manado, 2022)
Learning Evaluation Management in Improving Graduate Quality at the Institute of Arabic Studies Ma'had Al-Birr Makassar. This study aims to establish the method and processes for conducting learning evaluations at the Ma'had Al-Birr Institute of Arabic Studies Makassar in order to improve the quality of graduates at Ma'had Al-Birr. In addition, define the elements that help and hinder the execution of the targeted learning evaluation. This study use descriptive qualitative research to collect data and information on learning assessment management in order to improve the quality of Ma'had Al-Birr graduates through observation, document studies, and interviews. The acquired data were evaluated using a descriptive procedure that included three concurrent streams of activities: data reduction or data simplification, data presentation or presentation, and lastly deriving conclusions or verification. The findings revealed that learning evaluation management at Ma'had Al-Birr Makassar had been successfully managed through planning, coordinating, executing, and overseeing. All parties, from the leadership team to the lecturers, are participating in the evaluation of learning at Ma'had Al-Birr, either directly or indirectly. In this scenario, the academic field plays a critical role in determining the effectiveness of the learning program at Ma'had Al-Birr, including learning assessment. There are supporting and inhibiting variables in the learning evaluation process at Ma'had Al-Birr, however keep in mind that in general, the learning assessment can be assured and responsible for its quality, thus these inhibiting factors do not greatly impact the learning evaluation process